Anatomical simulation analysis of pancreaticobiliary junction in occult pancreaticobiliary reflux: based on Fluent study - LÜ Beining, HOU Nianzong, XIANG Yukai, DA Xuanbo, YANG Yulong, TIAN Fuzhou (Waike lilun yu shijian)
Objective Computational fluid dynamics software combined with finite element method was used to conduct 2D numerical simulation of pancreaticobiliary junction, and analyze the influence of biliopancreatic ampullary diaphragm, opening direction and shape of duodenal papilla on occult pancreaticobiliary reflux(OPBR). Methods The data of anatomical structure of pancreaticobiliary junction were obtained from online information. Pancreaticobiliary junction was reconstructed in 2D by computational fluid dynamics Fluent 2020R2 software. Different models were drawn for the pancreaticobiliary junction according to the following parameters: biliopancreatic ampullary diaphragm (with/without), opening direction of duodenal papilla(biased to the side of bile duct/central/biased to the side of pancreatic duct). A total of 6 models were used to analyze the risk factors for OPBR. Results When the anatomical structure of the biliopancreatic duct confluence was normal, that was, the ampullary diaphragm exists, no matter how the shape of the duodenal papilla and the opening direction changed, there was no pancreaticobiliary reflux. When the common channel was >5 mm due to the absence of the ampullary diaphragm and duodenal papilla was biased to the side of bile duct, a small amount of pancreatic juice refluxed into the lower end of the bile duct. When the common channel was >5 mm due to the absence of the ampullary diaphragm and duodenal papilla open position was in the middle of the biliopancreatic duct, the velocity and flow rate of pancreatic juice entering bile duct increased, and the degree of reflux was maintained at the lower end of the bile duct. When the common channel was >5 mm due to the absence of the ampullary diaphragm and the duodenal papilla was biased to the side of pancreatic duct, the degree of pancreaticobiliary reflux was more serious, and pancreatic juice reflux was observed throughout the entire bile duct. On the basis of this reflux model, the length of common channel of biliopancreatic duct was shortened, and the opening of outflow tract was enlarged, and the phenomenon of pancreaticobiliary reflux disappeared. Conclusions Based on the Fluent study, it is found that anatomical structures such as ampullary diaphragm and duodenal papilla were closely related to the occurrence of OPBR. Pancreaticobiliary reflux can be terminated by shortening the common channel length of pancreaticobiliary junction and expanding the opening of outflow tract.